Minimal model estimation of glucose absorption and insulin sensitivity from oral test: validation with a tracer method - Dalla Man, Chiara; Caumo, Andrea; Basu, Rita; Rizza, Robert; Toffolo, Gianna; Cobelli, Claudio (American journal of physiology: endocrinology and metabolism, 2004)
1 Department of Information Engineering, University of Padova, I-35131 Padova; 2 San Raffaele Scientific Institute, 20131 Milano, Italy; and 3 Division of Endocrinology, Diabetes, Metabolism, and Nutrition, Department of Internal Medicine, Mayo Clinic and Foundation, Rochester, Minnesota 55905 Submitted 10 July 2003 ; accepted in final form 30 April 2004 Measuring insulin sensitivity during the physiological milieu of oral glucose perturbation, e.g., a meal or an oral glucose tolerance test, would be extremely valuable but difficult since the rate of appearance of absorbed glucose is unknown. The reference method is a tracer two-step one: first, the rate of appearance of glucose (R a meal ref ) is reconstructed by employing the tracer-to-tracee ratio clamp technique with two tracers and a model of non-steady-state glucose kinetics; next, this R a meal ref is used as the known input of a model describing insulin action on glucose kinetics to estimate insulin sensitivity (S I ref ). Recently, a nontracer method based on the oral minimal model (OMM) has been proposed to estimate simultaneously the above quantities, denoted R a meal and S I , respectively, from plasma glucose and insulin concentrations measured after an oral glucose perturbation. This last method has obvious advantages over the tracer method, but its domain of validity has never been assessed against a reference method. It is thus important to establish whether or not the "nontracer" R a meal and S I compare well with the "tracer" R a meal ref and S I ref . We do this comparison on a database of 88 subjects, and it is very satisfactory: R a meal profiles agree well with the R a meal ref and correlation of S I ref with S I is r = 0.86 ( P < 0.0001). We conclude that OMM candidates as a reliable tool to measure both the rate of glucose absorption and insulin sensitivity from oral glucose tests without employing tracers. glucose kinetics; rate of appearance of glucose; tracer; meal; insulin resistance Address for reprint requests and other correspondence: C. Cobelli, Dept. of Information Engineering, Univ. of Padova, Via Gradenigo 6/B, I-35131 Padova, Italy (E-mail: cobelliatdei.unipd.it )